Programa de apoio a planos de reestruturação e expansão das universidades federais (REUNI) contextos, condicionantes e resultados de sua implementação - Trevizan, Edevania (Editora Oficina Universitária, 2022)
The book deals with changes resulting from its implementation of the Support Program for Restructuring and Expansion Plans for Federal Universities (Reuni). Addressing questions of planning and execution of public policies and revealing the structuring assumptions in the context of the elaboration of policies for education. More specifically, the analysis highlights the goals defined between the Ministry of Education and the universities, and their implications for the curricular reformulation proposed by Reuni, which brought with it a restructuring of academic careers aimed at establishing flexible itineraries. Which are intertwined with the interests of the capitalist system's mode of production. Despite being a successful program from the point of view of expanding access to public higher education, Reuni was implemented in the form of management contracts, with a defined deadline for completion, leaving universities without resources to maintain the expansion achieved, which has been observed since 2013, with the reduction in the budget of institutions and federal investments, which has hampered the development of teaching and research in universities.